Compass—Canada’s first child psychiatry access program: Implementation and lessons learned - Vivian W. L. Tsang; Michelle C. Q. Lin; Natalie Huang; Sally Tsoi; Jack Hu; Sonja Sinclair; Priya Watson; Susan Baer; Roberto Sassi (PLoS ONE, 2025)
Background There is a lack of mental health and substance use providers for youth in BC, particularly in rural and remote areas. To address these gaps, Canada’s first child psychiatry access program, BC Children’s Hospital Compass Program, was developed in 2018 to support providers across the province in providing evidence-based mental health and substance use care to youth under 25. This article describes the program’s first five years and provides an overview of its creation, utilization, and clinical uses. Methods Quantitative data collected by the Compass Program from September 2018 through September 2023 were analyzed. Participation and utilization of the service by providers in the province were analyzed and descriptive statistics, including means with standard deviations for quantitative variables have been used to describe demographic and other medical factors related to participants. Findings A total of 2336 new providers have been enrolled since Compass’ inception. Number of clinical calls into Compass remained steady over the five-year period with an average of 1085 individual providers served per year. Service use is highest in Vancouver Coastal Region (27.3%), followed by Northern Health (21.4%), Interior (15.7%), Vancouver Island (14.5%), and Fraser (13.4%), and Yukon (0.3%). General practitioners make up over a third of all encounters (34.6%), followed closely by pediatrician encounters making up 27.5% of total encounters from 2018–2023. These two provider types comprise over 60% of all encounters over the 5-year timespan. Encounters with other provider types were less common, with the third most common encounter being Child and Youth Mental Health (CYMH) clinicians, totalling 8.6% of total encounters. 37.6% of encounters were for male patients and 42.9% for female patients with 6.8% reporting “Other” genders and 12.7% declining to answer. Medication concerns are the most common reason for accessing Compass, regardless of gender. Therapy questions, resource coordination issues, and diagnostic clarification followed in frequency, comprising a similar amount of consults. Compass consultations have the potential to benefit three groups of people: the specific patient being consulted on, the provider requesting the consultation, as well as the provider’s colleagues who might benefit from peer consultation. Conclusions Capacity building is important given Compass receives calls from rural and remote areas where there are no psychiatrists or child psychiatrists where general practitioners and clinicians regularly work with patients along the entire spectrum of mental health and substance use disorders.